Pharmacotherapy for treating metastatic clear cell renal cell carcinoma. (22nd January 2017) - Porta, Camillo; Chiellino, Silvia; Ferrari, Alessandra; Mariucci, Sara; Liguigli, Wanda
ABSTRACT: Introduction : Over the past decade metastatic renal cell carcinoma (RCC) treatment landscape has dramatically evolved from the era of cytokines-based immunotherapy (which benefited very few patients, at the expenses of high toxicities) to the present era of targeted agents and novel immunotherapeutics, greatly improving the prognosis of our patients. Areas covered : Here we have reviewed the present status of the medical treatment of metastatic RCC. To do this, we interrogated the Medline database, as well as the proceedings of the main Oncological and Urological conferences for the relevant trials coducted so far. Expert opinion : Despite all the advances made in these relatively few years, further improvements are needed, since none of the available agents proved able to cure even a sigle metastatic RCC patient. In particular, advances are awaited from the results of ongoing trial of combinations of different immune checkpoint inhibitors and of immune checkpoint inhibitors with anti-VEGF/VEGFRs agents. Furthermore, a better understanding of the molecular escape pathways used by the tumor to overcome VEGFR blockade or immune activation will hopefully bring soon to the clinic more active, tailored treatments, to be used in second line and beyond.